2020
DOI: 10.2147/ott.s274394
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinicopathological Characteristics of TZAP Expression in Colorectal Cancers</p>

Abstract: Purpose The zinc finger protein, ZBTB48, is a telomere-associated protein. It was renamed as telomeric zinc finger-associated protein (TZAP) binding to elongated telomeres. However, its expression level was not measured in cancers. Patients and Methods We analyzed TZAP mRNA levels in 60 colorectal cancers (CRC) and its correlation with telomere length and TERT was studied. Results TZAP mRNA in CRC was higher statistically than that in paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
(25 reference statements)
2
14
1
Order By: Relevance
“…Insufficient TZAP expression may induce longer telomere length [20]. A strong correlation between longer telomeres and increased risk of NSCLC, especially AD, has been reported [21][22][23].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Insufficient TZAP expression may induce longer telomere length [20]. A strong correlation between longer telomeres and increased risk of NSCLC, especially AD, has been reported [21][22][23].…”
Section: Discussionmentioning
confidence: 98%
“…When its expression is not sufficient in cancer cells, cells with longer telomeres can easily change into immortal cells, anticipating cancer development [4,5]. In this way, TZAP expression could mediate telomere trimming, thereby restricting abnormally long telomeres [15][16][17][18][19][20]. However, TZAP In SCC, TZAP expression did not have any prognostic values of OS (2215.91 ± 174.72 vs. 1946.47 ± 148.77 days, p = 0.805; Figure 3A) and DFS (2614.32 ± 215.95 vs. 2812.18 ± 218.12 days, p = 0.679; Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting finding in this study is that only the third ZnF of Zbtb34 binds to the telomeres, while the functions of the other two ZnFs are unclear. It was found in previous studies that ZBTB48 and ZBTB10 were involved in the progression of different cancers [ 18 , 19 ]. Zbtb34 has also been shown to play a role in tumor growth as a transcriptional repressor [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that TERT overexpression contributes to cancer progression [ 24 ]. Therefore, YAP1 promotes TERT expression, which may contribute to tumor progression [ 25 ]. However, several studies have highlighted the importance of TERC in cancer because of findings indicating that TERC expression may be highly upregulated in a variety of cancers [ 26 30 ].…”
Section: Introductionmentioning
confidence: 99%